Vibrational and electronic circular dichroism of Δ-TRISPHAT [tris(tetrachlorobenzenediolato)phosphate(V)] anion - Bas, Delphine; Bürgi, Thomas; Lacour, Jerôme; Vachon, Jerôme; Weber, Jacques (My University, 2005)
Herein is reported an experimental and theoretical study of the circular dichroism properties of TRISPHAT (1) anion. ECD analysis of the [tetramethylammonium][Δ-1] salt confirms the absolute configuration assignment obtained through X-ray crystallographic analysis of the parent cinchonidium salt. The structure, infrared, and vibrational circular dichroism (VCD) spectra derived from density functional theory (DFT) calculations are compared with experimental data.
Keywords: Δ-TRISPHAT anion; X-ray crystallography; CD properties; DFT; VCD